1988
DOI: 10.1111/j.1558-5646.1988.tb04127.x
|View full text |Cite
|
Sign up to set email alerts
|

A MOLECULAR REEXAMINATION OF INTROGRESSION BETWEEN HELIANTHUS ANNUUS AND H. BOLANDERI (COMPOSITAE)

Abstract: Abstract. -Heiser (1949) hypothesized that a weedy race of Helianthus bolanderi had originated by the introgression of genes from H. annuus into a serpentine race of H. bolanderi. Although Heiser's investigation of these species is frequently cited as one ofthe best examples ofintrogression in plants, definitive evidence of gene exchange is lacking (Heiser, 1973). To determine whether the weedy race of H. bolanderi actually originated via introgression, we analyzed allozyme, chloroplast-DNA (cpDNA), and nucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1989
1989
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(2 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…This is particularly true for taxa of Erythroxylum where the obstacles demarcated by Plowman and Rivier (1) still exist today. Several methodologies are available that address the preservation of plant material for molecular systematic studies for plants indigenous to tropical regions (2)(3)(4)(5)(6) as well as descriptions of their performance (5,7,8). The most efficient method for preserving plant material is with the use of liquid nitrogen, but this imposes inherent problems in tropical environments (2).…”
Section: Introductionmentioning
confidence: 99%
“…This is particularly true for taxa of Erythroxylum where the obstacles demarcated by Plowman and Rivier (1) still exist today. Several methodologies are available that address the preservation of plant material for molecular systematic studies for plants indigenous to tropical regions (2)(3)(4)(5)(6) as well as descriptions of their performance (5,7,8). The most efficient method for preserving plant material is with the use of liquid nitrogen, but this imposes inherent problems in tropical environments (2).…”
Section: Introductionmentioning
confidence: 99%
“…Early studies documented hybrid swarms between different sunflower species ( Heiser 1947 ; Heiser 1949a ; Heiser 1951 ), demonstrating that chromosomal rearrangements contributed to hybrid sterility ( Chandler et al 1986 ; Lai et al 2005 ), and speculated on possible ecotypes and species that might be the products of hybridization ( Heiser 1949b ; Heiser 1958 ; Rieseberg 1991 ). Later molecular phylogenetic work and early low-resolution genomic studies supported some of these hypotheses ( Rieseberg, Beckstrom-Sternberg, et al 1990 ; Yatabe et al 2007 ), but not others ( Rieseberg et al 1988 ), and also suggested new hypotheses, including the putative origins of three homoploid hybrid species ( Rieseberg 1991 ). Here, we have taken advantage of new high-resolution genomic data and computational methods to further explore the role of hybridization in sunflower evolution.…”
Section: Discussionmentioning
confidence: 99%